Optimalisasi Visual Feed Instagram Sebagai Strategi Pemasaran Digital Pada UMKM Manda - Dinda Fatimah Azzahra Dinda Fatimah Azzahra; Marsanda Lasmita Romadina Marsanda Lasmita Romadina; Delliyana Isfahany Delliyana Isfahany; Tasya Augustiya Tasya Augustiya (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2026)
This community service activity was carried out at MSME Manda (Sundanese Food), a micro enterprise that specializes in producing Sundanese snacks, with flagship products in the form of beling chips and other product variants. The purpose of this activity is to help improve the effectiveness of digital marketing through content optimization by organizing social media feeds, especially Instagram, as a more structured and consistent promotional tool. Based on initial observations, MSME Manda has utilized social media platforms such as Instagram and TikTok as online sales tools, but its function has not been optimal because promotional content is still inconsistent and has not been strategically designed, so that the lack of interaction on social media with consumers has not been able to encourage an increase in online purchases. The method of implementing the activity is carried out through three stages, the first stage is pre-implementation by identifying the initial conditions of the business, the second stage is implementation in the form of designing and implementing a digital marketing optimization strategy, the final stage is evaluation as an assessment of the suitability of the implemented strategy with business needs and audience characteristics. Activities carried out include optimizing the visual feed of Instagram as a digital marketing tool. The results of this activity show positive changes, with the implementation of visual consistency through the determination of color, typography, and structured feed layout which strengthens brand identity and supports more positive perceptions of brand quality and credibility. These changes also encouraged audience engagement, such as following the account and exploring products further. The use of interactive content and a balance between entertainment and information has also been effective in engaging audiences and expanding brand reach.